Transfer prices assignment with integrated production and marketing optimization models - Enrique Parra (Journal of Industrial Engineering and Management (JIEM), 2018)
Purpose: In decentralized organizations (today a great majority of the large multinational groups), much of the decision-making power is in its individual business units-BUs-. In these cases, the management control system (MCS) uses transfer prices to coordinate actions of the BUs and to evaluate their performance with the goal of guaranteeing the whole corporation optimum. The purpose of the investigation is to design transfer prices that suit this goal. Design/methodology/approach: Considering the results of the whole company supply chain optimization models (in the presence of seasonality of demand) the question is to design a mechanism that creates optimal incentives for the managers of each business unit to drive the corporation to the optimal performance. Mathematical programming models are used as a start point. Findings: Different transfer prices computation methods are introduced in this paper for decentralised organizations with two divisions (production and marketing). The methods take into account the results of the solution of the whole company supply chain optimization model, if exists, and can be adapted to the type of information available in the company. It is mainly focused on transport costs assignment. Practical implications: Using the methods proposed in this paper a decentralized corporation can implement more accurate transfer prices to drive the whole organization to the global optimum performance. Originality/value: The methods proposed are a new contribution to the literature on transfer prices with special emphasis on the practical and easy implementation in a modern corporation with several business units and with high seasonality of demand. Also, the methods proposed are very flexible and can be tuned depending on the type of information available in the company.
Keywords: 650; transfer price; optimization models; decentralized organizations